Changing face of robot‐assisted radical prostatectomy in Melbourne over 12 years. Issue 3 (18th September 2017) - Sathianathen, Niranjan J.; Lamb, Alastair D.; Lawrentschuk, Nathan L.; Goad, Jeremy R.; Peters, Justin; Costello, Anthony J.; Murphy, Declan G.; Moon, Daniel A.
Abstract : Background: This study aims to characterize the trends in disease presentation for robot‐assisted radical prostatectomy (RARP) over a 12‐year period in Melbourne, Australia. Methods: All patients undergoing an RARP between 2004 and October 2016 while under the care of six high‐volume surgeons were included in this study. Data were collected prospectively regarding patient demographics and clinical details of their cancer. Results: Over the 12‐year time span of the study, 3075 men underwent an RARP with a median age of 63.01 years. Temporal analysis demonstrated that the median age of patients undergoing prostatectomy advanced with time with the median age in 2016 being 65.51 years compared with 61.0 years in 2004 ( P < 0.001). There was also a significant trend to increased D'Amico risk groups over time with the percentage procedures for high‐risk patients increasing from 12.6% to 28.10% from 2004 to 2016 ( P < 0.001). Upgrade rates between biopsy and pathological Gleason grade scoring significantly trended down over the period of the study ( P < 0.001). There was also a shift to increased pathological stage over the 12 years with 22.1% of men having T3 disease in 2004 compared with 49.8% in 2016. Conclusion: Our analysis demonstrates increasing treatment of older men with higher risk tumours, consistent with international trends. While this largely reflects a shift in case selection, further work is needed to assess whether the stage shift may relate partially to a decline in screening and increased presentation of higher risk disease.